Values, institutional culture and recognition of prior learning - Jacobs, A.H.M. (South African Journal of Higher Education, 2020)
ABSTRACT In this paper, I draw a link between values, institutional culture and the Stellenbosch University (SU) Regulation for Recognition of Prior Learning (RPL) and Credit Accumulation Transfer (CAT). I do this because the Regulation endorses the values of lifelong learning and the redress of inequalities. In turn, values form an important part of institutional culture. I use the ‘values’ element of a four-part theoretical framework developed in a conceptual analytic study of institutional culture in higher education to analyse the SU Regulation for RPL and CAT. The study employed critical hermeneutics as research methodology, which exposed the hidden meanings of and revealed other ideas of ‘institutional culture’. My analysis confirms a gap between the intentions of RPL and the way in which it plays out in practice. There is little evidence of significant strategies to address the challenges of RPL. Values related to RPL need to find expression in concrete strategies; otherwise, RPL will remain a challenging process. My analysis highlights the important role of institutional culture in RPL and CAT. Cultural systems (including institutional culture) shape the nature of practice concerning and attitudes towards RPL. Keywords: values, higher education, policy, institutional culture, RPL, CAT